Open-circuit respirometry: a historical review of portable gas analysis systems - Macfarlane, Duncan J. (European journal of applied physiology, 2017)
Scientists such as physiologists, engineers, and nutritionists have often sought to estimate human metabolic strain during daily activities and physical pursuits. The measurement of human metabolism can involve direct calorimetry as well as indirect calorimetry using both closed-circuit respirometry and open-circuit methods that can include diluted flow chambers and laboratory-based gas analysis systems. For field studies, methods involving questionnaires, pedometry, accelerometery, heart rate telemetry, and doubly labelled water exist, yet portable metabolic gas analysis remains the gold standard for most field studies on energy expenditure. This review focuses on research-based portable systems designed to estimate metabolic rate typically under steady-state conditions by critically examining each significant historical innovation. Key developments include Zuntz’s 1906 innovative system, then a significant improvement to this purely mechanical system by the widely adopted Kofranyi–Michaelis device in the 1940s. Later, a series of technical improvements: in electronics lead to Wolf’s Integrating Motor Pneumotachograph in the 1950s; in polarographic O 2 cells in 1970–1980’s allowed on-line oxygen uptake measures; in CO 2 cells in 1990s allowed on-line respiratory exchange ratio determination; and in advanced sensors/computing power at the turn of the century led to the first truly breath-by-breath portable systems. Very recent significant updates to the popular Cosmed and Cortex systems and the potential commercial release of the NASA-developed ‘PUMA’ system show that technological developments in this niche area are still incrementally advancing.